The Early Recovery of Cognitive Function After Total-Hip Replacement Under Hypotensive Epidural Anesthesia. Issue 2 (1st March 2005) - Sharrock, Nigel E.; Fischer, Gabriel; Goss, Selena; Flynn, Erin; Go, George; Sculco, Thomas P.; Salvati, Eduardo A.
Abstract : Background and Objectives: Recovery of cognitive function immediately after major surgery has not been previously reported, partly because of residual drug effects and pain. Methods: Changes in cognitive function were assessed using the Stroop Color and Word Test (SCWT), which was performed preoperatively, and 1 and 2 hours after total-hip replacement performed under hypotensive epidural anesthesia. In this case series, patients were sedated with propofol alone and had a lumbar plexus block performed at the end of surgery. Results: The SCWT was completed in 52 of 55 patients at either 1 or 2 hours after surgery. A significant reduction in cognitive function was noted 1 hour after surgery but a return toward baseline occured 2 hours after surgery. Age older than 70 years adversely affected recovery of cognitive function, but neither the preoperative diagnosis of hypertension nor the degree or duration of intraoperative hypotension (mean arterial pressure less than 45 mmHg) influenced cognitive function. Conclusion: The Stroop Color and Word Test can be used to assess change in cognitive function immediately after surgery. Total-hip replacement performed under regional anesthesia with propofol sedation enables recovery of cognitive function (as assessed by SCWT) 2 hours after surgery.